The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.14402/jkamprs.2014.36.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Necrotizing Fasciitis Caused by Dental Infection

Abstract: Necrotizing fasciitis (NF) is defined as rapidly progressive necrosis of subcutaneous fat and fascia. Although NF of the face is rare, its mortality rate is nearly 30%. It usually originates from dental infection and can lead to involvement of the neck, mediastinum, and chest wall. Complications resulting from pre-existing systemic diseases can increase the mortality rate. Known complication factors for NF include diabetes, malnutrition, advanced age, peripheral vascular disease, renal failure, and obesity. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In the clinic of maxillofacial surgery, abscesses and cellulitis of the maxillofacial area and neck, in terms of frequency of their occurrence, occupy one of the first places. [18][19][20][21][22][23][24][25][26][27][28][29][30] In recent years, the number of patients with this pathology has increased significantly, the course y of the process has worsened, which often leads to such severe complications as mediastinitis, sepsis, facial vein thrombosis of the face and brain sinuses. Thus, the relevance of this research topic does not cause doubts.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic of maxillofacial surgery, abscesses and cellulitis of the maxillofacial area and neck, in terms of frequency of their occurrence, occupy one of the first places. [18][19][20][21][22][23][24][25][26][27][28][29][30] In recent years, the number of patients with this pathology has increased significantly, the course y of the process has worsened, which often leads to such severe complications as mediastinitis, sepsis, facial vein thrombosis of the face and brain sinuses. Thus, the relevance of this research topic does not cause doubts.…”
Section: Discussionmentioning
confidence: 99%
“…CNF mainly originates from odontogenic infections of molar teeth. 7,8 Tung-Yiu 9 reported that, of all the odontogenic infections admitted to their clinic in a period of 10.5 years, the incidence of CNF was 2.6% and mandibular molars were the most common source, probably because the roots of first and second molar teeth are in close relationship with submandibular and submassateric spaces. 3 However, in the present case, the source of the odontogenic infection was the right mandibular canine tooth.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of NF in the maxillofacial region is very rare and is generally only seen in about 2.5%-5% of all cases. [12] It is commonly associated with systemic diseases such as DM.13 NF in the maxillofacial region is caused by an odontogenic infectious process and can also be caused by tonsillopharyngitis, or salivary gland infection. [11,14]…”
Section: Introductionmentioning
confidence: 99%